Emission Factors of PAHs Components and Bioreactivity in PM2.5 from Biomass Burning - Xinye Zhu; Kin-Fai Ho; Tzu-Ting Yang; Vincent Laiman; Jian Sun; Zhenxing Shen; Hsiao-Chi Chuang (Aerosol and Air Quality Research)
Abstract Biomass burning releases fine particulate matter (PM2.5), water-soluble inorganic ions (WSIs), metal elements, polycyclic aromatic hydrocarbons (PAHs) and other compounds, and it is one of the largest sources of carbonaceous aerosols. The lungs experience negative health impacts from exposure to PM2.5; however, it is uncertain how PM2.5 emitted from biomass burning affect the human lung alveolar epithelium. This study investigated emission factors of PM2.5 from biomass burning and PM2.5 bioreactivity in human alveolar epithelial A549 cells. Emission factors were measured from biomass samples included maize straw (MS), wheat straw (WS), wood branches (WBs), MS briquettes (MSBs), MSB charcoal (MSC), WS briquettes (WSBs), WSB charcoal (WSC), WB briquettes (WBBs), and WBB charcoal (WBC). A549 cells were exposed to biomass PM2.5 at 0 and 50 µg mL–1 for 24 h, and the expression of Yes-associated protein (YAP), phosphorylated (p)-YAP, transcription coactivator with a PDZ-binding motif (TAZ), p-TAZ, E-cadherin, and high mobility group box 1 (HMGB1) proteins were assessed by Western blotting. We found that MSC, WSC, WSBs, and WBs had higher PM2.5 emission factors. MS has the highest emission factors of polycyclic aromatic hydrocarbons (PAHs) among all the biomass PM2.5, especially FLU (26.46 mg kg–1) and PYR (26.93 mg kg–1). There were 48.30% of PM2.5 was able to deposit in the alveolar area with a concentration of 32.25 µg m–3 estimated by a multiple-path particle dosimetry (MPPD) model. We observed decreases in p-YAP/YAP and HMGB1 expressions after biomass PM2.5 exposure. YAP were positively correlated with ANT, PHE, 1-MP, FLU, PYR, 3,6-DP, BaA, CHR, BbF, BkF, BaP, BeP, PER, IcdP, BghiP, and DahA (p < 0.05). In conclusion, PAHs in biomass PM2.5 contribute to cytotoxicity on A549 cells. PAHs in PM2.5 with high emission factors from biomass burning could cause significant human pulmonary deteritious health effects after inhalation.